Perbandingan Pengaruh Sistem Surveilans Berbasis Elektronik dan Paper Based Terhadap Kompetensi Pencatatan dan Kemampuan Deteksi Risiko Hais oleh Perawat Di Rumah Sakit Awal Bros Batam: Comparison of the Effect of Electronic and Paper-Based Surveillance Systems Paper Based Surveillance System on Recording Competency and Detection Ability of Risk of Hais by Nurses at Awal Bros Hospital Batam - Novita Simbolon; Hema Malini; Sri Muharni (NERS Jurnal Keperawatan, 2019)
HAIs surveillance is a supervision that includes data collection, analysis, interpretation and dissemination, which is currently developing into an electronic-based approach. This electronic-based surveillance is assumed to be able to provide higher data quality, faster and easier. However, this still needs to be proven further. The purpose of this study was to determine the effect and comparison of paper and electronic based on the system of recording and detecting risk of HAIs. This type of research is quantitative research with Quasi design Pre test - Post test Two Group, with a total sampling of 239 nurses. Methods of collecting data using instruments in the form of questionnaires to measure the nurses’ competency and the recording system. As an intervention carried out the implementation of electronic and paper-based surveillance for two weeks at the Awal Bros Batam Hospital. Data analysis was performed using the Wilcoxon Test to test the differences and Mann Whitney to test the effect. The results of the study illustrate the differences in nurses' competencies before and after HAIs surveillance training, illustrating the significant influence on the HAIs recording and detection system before and after the application of electronic and paper based. It is recommended to develop electronic-based software for recording and detecting HAIs systems connected to the Hospital Management Information System (SIMRS).